THE COMBINED IMPACT OF HIGH DEBT LEVELS AND NEGATIVE EARNINGS ON THE VALUE RELEVANCE OF ACCOUNTING INFORMATION - Saputra, Dany Adi (Juremi: Jurnal Riset Ekonomi, 2025)
This study examines how high debt levels and negative earnings affect accounting information's value relevance. Positive correlations between stock prices, book value of equity per share (BVPS), and earnings per share (EPS) demonstrate the value relevance of accounting information. The sample includes 1,209 the Indonesia Stock Exchange (IDX)-listed enterprises in 2018-2019, in the period before the Covid-19 Pandemic. The hypotheses were tested using multiple linear regression analyses. The results prove the worth of BVPS and EPS. Next, high debt levels do not cause BVPS or EPS to lose relevance. Negative earnings reduce the relevance of BVPS and EPS. Low debt levels paired with negative earnings lower the value relevance of EPS but not BVPS. High debt levels and negative earnings lead BVPS and EPS to lose relevance. The observation period before the COVID-19 pandemic may affect the value relevance of EPS and BVPS in this investigation. This sample was chosen to avoid pandemic-related outcomes. Future research might evaluate pandemic effects. This finding demands management to control debt and prevent losses. These findings can inform authorities about excessive debt and negative earnings, such as in "special notices" on the Indonesia Stock Exchange's website. This analysis contributes to the literature by showing how high debt levels and company losses affect EPS and BVPS value relevance